2014
DOI: 10.4172/2329-8790.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Insidious Renal Damage in Patients with Thalassemia Major: Is it More Serious than Appreciated?

Abstract: Aim: To investigate early renal injury in thalassemia major patients by using novel serum markers and demonstrate the factors leading to renal injury. Material and Methods: Seventy-one thalassemia major patients (37 males) who were on regular transfusion and chelation programme with deferasirox have been enrolled in this study. Thirty-five healthy children of the same age served as a control group. Serum urea-creatinine, electrolytes, cystatin C and glomerular filtration rate were all noted in our cohort and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(31 reference statements)
1
4
0
1
Order By: Relevance
“…In the current study, 56 patients (59.6%) had elevated Cystatin-C. Similarly, in previous study done by Gokce et al, 16 mean serum Cystatin-C levels were elevated in 46 (64.7%) of the studied β-TM patients in Turkey.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, 56 patients (59.6%) had elevated Cystatin-C. Similarly, in previous study done by Gokce et al, 16 mean serum Cystatin-C levels were elevated in 46 (64.7%) of the studied β-TM patients in Turkey.…”
Section: Discussionsupporting
confidence: 89%
“…The source of elevated serum AST among patients with β-TM having elevated Cystatin-C serum levels could be because of the pathology of hemolysis or of hepatic origin, secondary to increased iron deposition or of muscular origin. 16 In a study performed in Iran by Sadeghi-Bojd et al, 18 high urinary levels of protein, calcium, phosphorous, uric acid, magnesium, and β2-microglobin were common signs among βTM patients and concluded that the pathology of β-TM can affect both renal tubules and glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin level should be maintained for a range of 9.5-10.5 g/dl in order to maintain growth and development in normal range until the age of 10-11, however over that age, a complication may occur due to iron overload and chronic anemia. Gokce et al [31] found that BTM patients with glomerular hyperfiltration had a median hemoglobin level of 8.6 g/dL (7,6-10,5 g/dL). This hemoglobin range cannot be extrapolated in all health facilities as it depends on individual health center protocol and availability of local resources.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding renal injury, several factors might play role in patients with thalassemia. Chronic hypoxia, ongoing hemolysis, iron overload owing to transfusions and possible nephrotoxicity of chelators are well-known reasons of the deterioration in renal functions [9] .…”
Section: Discussionmentioning
confidence: 99%